Current Status and Future Directions of Bacteria-Based Immunotherapy - Quan Tang; Quan Tang; Xian Peng; Bo Xu; Bo Xu; Xuedong Zhou; Xuedong Zhou; Jing Chen; Jing Chen; Lei Cheng; Lei Cheng (Frontiers in Immunology, 2022)
With the in-depth understanding of the anti-cancer immunity, immunotherapy has become a promising cancer treatment after surgery, radiotherapy, and chemotherapy. As natural immunogenicity substances, some bacteria can preferentially colonize and proliferate inside tumor tissues to interact with the host and exert anti-tumor effect. However, further research is hampered by the infection-associated toxicity and their unpredictable behaviors in vivo. Due to modern advances in genetic engineering, synthetic biology, and material science, modifying bacteria to minimize the toxicity and constructing a bacteria-based immunotherapy platform has become a hotspot in recent research. This review will cover the inherent advantages of unedited bacteria, highlight how bacteria can be engineered to provide greater tumor-targeting properties, enhanced immune-modulation effect, and improved safety. Successful applications of engineered bacteria in cancer immunotherapy or as part of the combination therapy are discussed as well as the bacteria based immunotherapy in different cancer types. In the end, we highlight the future directions and potential opportunities of this emerging field.